1987
DOI: 10.1126/science.2820055
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes and Lipoxins: Structures, Biosynthesis, and Biological Effects

Abstract: Arachidonic acid is released from membrane phospholipids upon cell stimulation (for example, by immune complexes and calcium ionophores) and converted to leukotrienes by a 5-lipoxygenase that also has leukotriene A4 synthetase activity. Leukotriene A4, an unstable epoxide, is hydrolyzed to leukotriene B4 or conjugated with glutathione to yield leukotriene C4 and its metabolites, leukotriene D4 and leukotriene E4. The leukotrienes participate in host defense reactions and pathophysiological conditions such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
1,270
0
25

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,161 publications
(1,307 citation statements)
references
References 50 publications
12
1,270
0
25
Order By: Relevance
“…In addition, we detected 5-LO expression in renal tissue that also exhibited positive staining for viral antigens in serial sections; 5-LO is an essential enzyme for the biosynthesis of leukotrienes, which are potent proinflammatory mediators (15). Recently, we demonstrated that HCMV induces 5-LO expression in vitro and in patients with inflammatory bowel disease (16).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, we detected 5-LO expression in renal tissue that also exhibited positive staining for viral antigens in serial sections; 5-LO is an essential enzyme for the biosynthesis of leukotrienes, which are potent proinflammatory mediators (15). Recently, we demonstrated that HCMV induces 5-LO expression in vitro and in patients with inflammatory bowel disease (16).…”
Section: Discussionmentioning
confidence: 85%
“…Both NO [2,20] and lipoxygenase products such as leukotrienes and hydroxy fatty acids [21][22][23] are messenger molecules which exhibit a variety of biologically relevant properties. So far no direct interaction of both pathways in mammalian cells has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Chiral purity of biologically derived hydroxylated fatty acids is typically attributed to the lipoxygenase (Lox) family [24][25][26][27][28][29][30][31] with preference usually shown for S-stereoisomer products. In the absence of Lox, however, free-radical mediated peroxidation of AA can yield a racemic mixture of each hydroxylated isomer.…”
Section: Resultsmentioning
confidence: 99%